Global inequalities in the double burden of malnutrition and associations with globalisation - Seferidi, Paraskevi (2022)
Funding Information: PS, AB-O, and CM are supported by the Biotechnology and Biological Sciences Research Council (grant reference BB/T009004/1). Publisher Copyright: © 2022 The Author(s). Published by Elsevier Ltd. This is an Open Access article under the CC BY 4.0 license